2014
DOI: 10.1111/medu.12597
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: the roles of social capital and ethnicity in medical student achievement

Abstract: ObjectivesWithin medical education, patterns of achievement indicate that white students outperform their ethnic minority peers. The processes behind these patterns have not been adequately investigated or explained. This study utilises social network analysis to investigate the impact of relationships on medical student achievement by ethnicity, specifically by examining homophily (the tendency to interact with others in the same group) by ethnicity, age and role. MethodsData are presented from a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
134
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 37 publications
3
134
1
2
Order By: Relevance
“…An important reason of this finding might be the academic and social stress that foreign students face due to adjustment problems (Rienties et al, 2012). Another reason might be the lack of social network that minimizes facilitative resources for success (Vaughan, Sanders, Crossley, O'neill, & Wass, 2014). In contrast to findings mentioned above, in a study among Malaysian university students, foreign students were found to be more successful than the natives (Ainin et al, 2015).…”
Section: Factors Of Tertiary Academic Success At Macrosystem Level Etcontrasting
confidence: 43%
See 1 more Smart Citation
“…An important reason of this finding might be the academic and social stress that foreign students face due to adjustment problems (Rienties et al, 2012). Another reason might be the lack of social network that minimizes facilitative resources for success (Vaughan, Sanders, Crossley, O'neill, & Wass, 2014). In contrast to findings mentioned above, in a study among Malaysian university students, foreign students were found to be more successful than the natives (Ainin et al, 2015).…”
Section: Factors Of Tertiary Academic Success At Macrosystem Level Etcontrasting
confidence: 43%
“…In a large cross-institutional comparative study at five business schools in the Netherlands, Rienties et al (2012) found native and foreign students were similarly successful. This similarity of success was also found in a study among an American medical university students (Vaughan et al, 2014). Rienties et al (2012) also noted that academic adjustment was the main predictor of academic success for all ethnic groups.…”
Section: Factors Of Tertiary Academic Success At Macrosystem Level Etmentioning
confidence: 49%
“…It might be that the negative effects on learning of ethnic homophily (the tendency to interact with others in the same group) which has been reported in medical students (Vaughan et al 2015; Woolf et al 2012) are more profound for this type of examinations. Ethnic homophily may cut off minority students from resources that facilitate learning (Vaughan et al 2015), which might be particularly important for an examination that requires a high level of self-organised, informal learning.…”
Section: Discussionmentioning
confidence: 90%
“…What makes lower achievers connect less with others when these connections would be quite useful? First, lower achievers may have difficulties in approaching their fellow students if they do not have the social skills necessary for asking support (Cleland et al 2005;Todres et al 2012;Vaughan et al 2015). Second, lower achievers may be excluded from the support of higher achievers when higher achievers select each other for academic support and only lower achievers remain available for lower achievers.…”
Section: Discussionmentioning
confidence: 99%